2017
DOI: 10.1002/star.201600324
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of two Arabidopsis starch dikinases in potato

Abstract: Starch phosphate esters influence physiochemical properties of starch granules that are essential both for starch metabolism and industrial use of starches. To modify properties of potato starch and understand the effect of starch phosphorylation on starch metabolism in storage starch, the starch dikinases from Arabidopsis thaliana, glucan water dikinase 2 and 3 (AtGWD2 and AtGWD3), were heterologously expressed in potato tubers (Solanum tuberosum) from two genetic backgrounds: the amylose-containing clone Kar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Heterologous expression of Arabidopsis thaliana GWD2 and GWD3 in potato tubers would alter starch granule morphology, but not change the starch phosphate content (Xu et al, 2018).…”
Section: Gwdmentioning
confidence: 97%
See 1 more Smart Citation
“…Heterologous expression of Arabidopsis thaliana GWD2 and GWD3 in potato tubers would alter starch granule morphology, but not change the starch phosphate content (Xu et al, 2018).…”
Section: Gwdmentioning
confidence: 97%
“…Additionally, suppressed GWD expression in transgenic potato lines would decrease PV, BD, and CPV, but had no significant effects on starch gelatinization (Wickramasinghe et al., 2009). Heterologous expression of Arabidopsis thaliana GWD2 and GWD3 in potato tubers would alter starch granule morphology, but not change the starch phosphate content (Xu et al., 2018).…”
Section: Biosynthesis Of Potato Starchmentioning
confidence: 99%
“…A third homologue of the potato GWD was identified in Arabidopsis thaliana by screening the Arabidopsis genome and named AtGWD3 . Xu et al introduced two starch dikinases ( AtGWD2 and AtGWD3 ) from Arabidopsis into two different potato cultivars and found that there was no significant increase in starch phosphate content, but modified starches showed changes in granule morphology. It was also found that sucrose synthase 4 (Susy4) was up‐regulated in transgenic tubers with AtGWD2 expression …”
Section: Transgenic Engineeringmentioning
confidence: 99%
“…This could be achieved through plant breeding program and/or biotechnological approach. For instance, in order to alter the amount of negative charge of starch granules, plant scientists can add or remove starch-attached phosphate groups (charged negatively) by manipulating the expression of key genes involved in starch biosynthesis (Lanahan and Basu, 2006; Schewe et al., 2007; Carciofi et al., 2011; Frohberg, 2012; Xu et al., 2017a,b, 2018). We firmly believe that such design can be realized through joint efforts from plant scientists and biorefinery scientist and will play an important role in elevating the starch biorefinery to new heights.…”
Section: Creating Novel Biorefinery Concepts Through a Cross-disciplimentioning
confidence: 99%